Analisis Overall Equipment Effectiveness untuk Meningkatkan Efektivitas Mesin Filling Multiline pada PT-XYZ (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
In the modern industrial era, operational effectiveness has become the main focus for manufacturing companies. PT-XYZ, a leading company in the production of food seasoning, faced challenges in increasing the effectiveness of their multiline filling machines. PT XYZ is a food seasoning company that uses mixer machines and filling machines. In multiline filling machines, the research results show that there are problems with high downtime, production speeds that are not optimal, and product defect levels that exceed tolerance limits. This research aims to analyze the calculation of Overall Equipment Effectiveness (OEE) on multiline filling machines at PT XYZ with the aim of increasing its effectiveness. The research method involves collecting data on machine availability, machine performance, and product quality produced by multiline filling machines. The data was analyzed using OEE calculations and identified the main causes of low machine effectiveness by applying OEE and Six Big Losses analysis. This research aims to help PT-XYZ increase machine productivity and achieve the set production MSA (Master Schedule Attainment) target. Improvements that recommend for this case include more intensive routine maintenance, as well as increased quality control. It is hoped that the implementation of these improvements can increase the OEE of multiline filling machines and overall production effectiveness at PT XYZ